Step 1: Distribute the 2 to the terms inside the parentheses.
2x + 16 = 2x + 8
Reasoning: When we multiply a number by a sum in parentheses, we distribute the multiplication to each term inside the parentheses.
Step 2: Simplify the equation by combining like terms on both sides.
2x + 16 = 2x + 8
Reasoning: The equation has the same terms on both sides, so we can combine like terms by adding or subtracting them.
Step 3: Subtract 2x from both sides of the equation to isolate the constant term.
2x - 2x + 16 = 2x - 2x + 8
16 = 8
Reasoning: By subtracting 2x from both sides, we eliminate the x term on the right side and isolate the constant term on the left side.
Step 4: The equation 16 = 8 is false.
Reasoning: The equation 16 = 8 is not true; there is no value of x that satisfies this equation. Therefore, there is no solution to the original equation.
Solve the equation justifying each step with the correct reasoning.
2(x+8)=2x+8
1 answer